Haliplanella Hand, 1956 (Anthozoa, Actiniaria): proposed conservation by suppression of Haliplanella Treadwell, 1943 (Polychaeta) [Case 3493] - Fautin, Daphne Gail; Hand, Cadet (deceased); Daly, Marymegan (Bulletin of Zoological Nomenclature, 2009)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the generic name Haliplanella Hand, 1956 for a widespread sea anemone by suppressing the senior name Haliplanella Treadwell, 1943 that was first, through an error, used for a group of polychaete annelids, was later put into synonymy, and is now no longer used.
World Polychaeta Database (WPolyDb)